ADPF 347 AND THE “UNCONSTITUTIONAL STATE OF AFFAIRS” OF BRAZIL’S PRISON SYSTEM – ADPF 347 E O “ESTADO DE COISAS INCONSTITUCIONAL” DO SISTEMA PRISIONAL BRASILEIRO - Sombra, Thiago Luís Santos (Espaço Jurídico Journal of Law [EJJL], 2016)
This essay aims at analyzing the main aspects related to a prison system’s lawsuit judged by the Brazilian Supreme Court in which the “Unconstitutional State of Affairs” adjudication technique was firstly examined. Challenging the base arguments that were presented in the ADPF 347, Justice Rapporteur Marco Aurélio, the article’s purpose is points out that there was not an institutional failure of both Legislative and Executive branches of government in order to justify a structural intervention for overcoming alleged barriers. A parallel with Colombian Supreme Court adjudication practices will be drawn in accordance with the legal transplants theory to understand how Brazil would achieve its reach just importing a structural injunction model that even in Colombia did not work in prisons. Keywords: Unconstitutional State of Affairs. Structural Injunction. ADPF 347. Brazil’s Supreme Court. Colombia’s Supreme Court. Legal Transplants.